The Influence Of Transformational Leadership On Employee Performance With Organizational Commitment As A Moderation Variable In Regional Financial And Asset Management Agency Mandailing Natal Regency - Abdul Hakim Nasution; Mesra B (International Journal of Management, Economic and Accounting, 2025)
Transformational leadership that is not implemented effectively and low organizational commitment can result in suboptimal employee performance and decreased loyalty to the organization. The purpose of this study is to find out and analyze the role of organizational commitment in strengthening the influence of transformational leadership on employee performance at the Regional Financial and Asset Management Agency of Mandailing Natal Regency. This research was conducted with a causal associative quantitative approach. The sample used was all ASN employees totaling 82 people. The results of data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) show that: 1) Transformational leadership has a positive and significant effect on employee performance with a T-statistic value of 2.563 > 1.96 and a P-value of 0.012 < 0.05; 2) Organizational commitment has a positive and significant effect on employee performance with a T-statistic value of 4.098 > 1.96 and a P-value of 0.000 < 0.05; and 3) organizational commitment did not significantly strengthen the influence of transformational leadership on employee performance with a T-statistical value of 0.562 < 1.96 and a P-value of 0.576 > 0.05. These findings confirm that in the context of this study, organizational commitment does not have a significant impact in strengthening the relationship between transformational leadership and employee performance. This suggests that while organizational commitment is important for performance, other factors may need to be considered to support the effectiveness of transformational leadership